Historical Significance in the South African History curriculum: An un-silencing approach (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The South African History Curriculum and Assessment Policy Statement (CAPS) emphasises the significance of History being that of empowering learners with historical skills and knowledge but there are critical gaps that this article tries to posit that affects quality teaching. The current global atmosphere of democracy with its emphasis on decolonisation, demands curriculum transformation. Such a context calls on ways of bridging the divide between theory and practice in education. CAPS-History emphasise the importance of teaching historical concepts but excludes the critical concept of Historical Significance which safeguards skills of interpretation and understanding why certain histories are in the official arena and others not. This article argues the CAPS-History curriculum has to be transformed to reflect the ideological changes that is experienced globally. The article uses critical discourse analysis in an attempt to uplift historical knowledge of Africans and to un-silence historically significant narratives. Data for the article was drawn from the observation of the author’s teaching experiences by using auto-ethnographical methods. The findings of the article are that CAPS-History have carried the implicit message that Historical Significance should be attributed to white males in power and selected events in history of people in positions of power and themes like symbols and symbolism, which are key in indigenous knowledge, are silenced. The conclusion of this article is that CAPS requires an epistemology that supports democratic principles of equality which calls upon unsilencing of certain historical narratives by employing Historical Significance as one of the critical concepts thinking concepts.
Keywords: Historical Significance; Un-silenced; History; Symbols; Symbolism; Curriculum and Assessment Policy Statement